Survival after radiofrequency ablation and/or chemotherapy for lung cancer and pulmonary metastases: a systematic review and meta-analysis - Yang, Ziyi; Lyu, Xia; Yang, Huilin; Wang, Bingbing; Xu, Dan; Huo, Lingyi; Zhang, Runzi; Huang, Yingjun; Diao, Benshu (Frontiers in Immunology, 2023)
Background: Radiofrequency ablation (RFA) and chemotherapy are used to treat lung cancer or pulmonary metastases, but no direct comparison of overall survival (OS) has been published. The present study aimed to assess the OS of RFA and/or chemotherapy in patients with lung cancer or pulmonary metastases who were not candidates for surgical resection. Methods: To identify relevant studies, the following databases were electronically searched from their inception to March 31, 2023: PubMed, Embase, Web of Science, Cochrane Library, Scopus, Ovid, ScienceDirect, SinoMed, China National Knowledge Infrastructure Database, Chongqing VIP Chinese Science and Technology Periodical Database, Wanfang Database, LILACS, ClinicalTrials.gov, and Chictr.org. Manual retrieval was also conducted. We used published hazard ratios (HR) if available or estimates from other survival data. Result: A total of 1387 participants from 14 trials were included in the final analysis. Patients treated with RFA combined chemotherapy significantly improved OS compared with chemotherapy alone (HR 0.50, 95% CI 0.41-0.61; p<0.00001), with an absolute difference at 12 months of 29.6% (95% CI 23.7 to 35.5), at 24 months of 19.2% (95% CI 10.1 to 28.2), and at 36 months of 22.9% (95% CI 12.0 to 33.7). The HR for OS with RFA plus chemotherapy versus RFA alone was 0.53 (95% CI 0.41-0.70; P<0.00001 ), corresponding to a 27.1% (95% CI 18.3 to 35.8), 31.0% (95% CI 19.9 to 41.9), and 24.9% (95% CI 15.0 to 34.7) absolute difference in survival at 12 months, 24 months, and 36 months, respectively. The HR of RFA versus chemotherapy was 0.98 (95% CI 0.60-1.60; P = 0.94), with an absolute difference at 12 months of 1.4% (95% CI -19.2 to 22.1), at 24 months of 7.8% (95% CI -11.3 to 26.8), and at 36 months of 0.3% (95% CI -13.2 to 13.8). The overall indirect comparison of OS for RFA versus chemotherapy was 0.95 (95% CI 0.72-1.26; P =0.74). Data on PFS were not sufficiently reported. Conclusion: RFA combined chemotherapy might be a better treatment option for patients with lung cancer or pulmonary metastases than chemotherapy alone or RFA alone. The comparison between RFA and/or chemotherapy remains to be specifically tested.